ASPEK BISNIS USAHA NGAMBING DI KELAPA GADING JAKARTA UTARA - Brastoro Brastoro; Elisabeth Vita Mutiarawati (Jurnal Manajemen, 2021)
The writing of the Ngambing business plan is due to the changing lifestyle of the general public who are interested in new, practical products that can support this lifestyle. So the author opened a goat satay box rice business which is rarely found. Ngambing has competitors in the same industry, but are presented with their own uniqueness. Therefore, an analysis of the industry and competitors has been carried out and the results can be seen the advantages and disadvantages of each business. Ngambing provides products in the form of goat satay rice boxes with various choices of Indonesian spices. And use a variety of marketing strategies. Ngambing has a production plan flow that involves internal and external parties. Ngambing plans the need for five employees to carry out its operational activities. The initial investment required by Ngambing is Rp. 695,868,373. Sources of funds obtained from personal savings and parents. Ngambing has considered the impacts and risks of existing businesses, and tries to minimize them according to applicable standards. From the results of the calculation of Net Present Value, Payback Period, Profitability Index, and Break Even Point are declared feasible to be run by the company. Keywords: NPV, Payback Period (PP), Profitability Index (PI), BEP.